CHARACTERISTICS ЩА REPRODUCTIVE ORGANS OF CASPIAN SEAL (PHOCA CASPICA, GMELIN, 1788) IN THE CONDITIONS OF ANTHROPOGENIC PRESSING - V. V. Volodina; M. P. Grushko; N. N. Fedorova (Юг России: экология, развитие)
Abstract. Aim. To study the morpho-functional state of reproductive organs of different-age specimens of the Caspian seal. Methods. We have analyzed the organs of the reproductive system of 26 females and 19 males of the Caspian seal, 29 of which are sexually mature specimens and 18 specimens are not sexually mature. The biological material was sampled during specialized research expeditions to the pre-winter herds in October-November 2012, 2014, 2015. The treatment of samples was carried out in accordance with the standard histology techniques.  Results. In organs of the reproductive system of investigated fishes scientists have revealed various pathologies. Sexually maturity of males in testicles had the next violations: hyalinosis of the vessel walls: the absence of the layer of spermatogone: pyknosis of kernels of sperm. Pathologies in tests of immature males were not essential. Sexually maturity females had the signs of glandular endometrial hyperplasia. It is noted the signs of sclerous-cystous ovaries. In the uterus of immature females were revealed pathological changes due to inflammatory reaction; in the feeding substance of the ovaries it was discovered a significant number of interstitial glands. Such violations were registered by a number of authors under chronic intoxication (ecotoxicity). Main conclusions. Immature individuals have not expressed pathological changes, which are less expressed than in older age groups. Increased elimination of germ cells is a result of the damaging effects on the reproductive system of animals. Arduous duty of functioning may cause of the violation of the reproductive potential of the population,that on the background of ecological problem can lead to further reduction in the number of Caspian seal.